Global production, processing and utilization of lentil: A review - Matina Joshi; Yakindra Timilsena; Benu Adhikari (Journal of Integrative Agriculture, 2017)
Lentil is a highly nutritious legume with an ample quantity of carbohydrates and good amount of proteins, minerals, vitamins, phytochemicals and fibres. Although it has been used as staple food since ancient times, its usage has been limited in developed countries, especially due to the lower protein digestibility, presence of anti-nutritional factors, flatulence and poor cooking qualities. Processing of lentils including dehulling and splitting and isolation of major fractions, e.g., proteins and starches are some of the strategies that can be adopted to add value and increase consumption of these legumes. This review paper intends to provide detailed overview of lentil's global production, nutritional composition and processing methods of lentil. Methods of isolation/characterization of lentil protein and starch and their subsequent application in foods are also presented.